(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The objective of the present study was to evaluate antiulcer potential of aqueous and ethanolic extract Clitoria ternatea in different experimental induced ulcer models in rats. In the present study different extracts [ethanolic (200 mg/kg and 400 mg/kg) and aqueous (200 mg/kg and 400 mg/kg) extract of whole plant were examined in Pylorus ligation and Indomethacin induced gastric ulcer in rats. Various parameters like volume of gastric acid secretion, pH, total acidity, ulcer index and antioxidant parameters were determined and compared between extract treated, standard and vehicle control group animals following ulcer induction. Among different dose of alcoholic extract, high dose showed significant antiulcer activity in Pylorus ligation and Indomethacin induced ulceration. The result of present study concluded that the alcoholic extract of whole plant of Clitoria ternatea has antiulcer activity in Pylorus ligation and Indomethacin induced gastric ulcer model in rats. The extract containing flavonoids show antiulcer activity, indicating the flavonoids component of the extract to be responsible for the activity of the extracts.